KEWENANGAN PEMERINTAH DAERAH DALAM PENGADAAN TANAH BAGI PELAKSANAAN PEMBANGUNAN UNTUK KEPENTINGAN UMUM - Kristian, Dikson; Suyatna, I Nyoman; Dahana, Cokorda Dalem (Kertha Negara : Journal Ilmu Hukum, 2014)
Government Authority in the implementation of land acquisition for the construction of a public interest in the Government authorities to provide land for the construction of the public interest . The problem that arises then is unclear rules governing the authority of the Government in the implementation of land acquisition for the construction of the public interest as well as legal protection for land rights holders affected by the land acquisition by the government. This journal normative method to approach the study of literature. In Article 6 of Law No. 12 The year 2012 is mentioned land acquisition for public interests held by the Government. Section 8 of Presidential Decree. 71 The year 2012 also mentioned that the Governor carry out a preparatory stage of land acquisition after receiving the land acquisition planning documents. Law No. 2 In 2012 and Presidential Decree. 71 The year 2012 is set on the deliberations, awarding damages, and filing a lawsuit for land rights holders. It can be concluded authority for the implementation of land acquisition for the construction of public interest under the authority of the Governor and the Provincial Government as the legal protection of the rights of the owner of the land is reflected through the regulation of deliberation, of compensation, and the provision of opportunity to file a lawsuit to the Administrative Court and to District Court.
Keywords: Government Authority, Land Acquisition, Public Interest